Development of Reading Literacy and Numeracy Assessment Instrument Incorporating Ethnoscience in Thermochemistry using Learning Management System for Critical Thinking Skills - Nasrul Adadi; Wiwi Siswaningsih; Triannisa Rahmawati; Dhea Lutvia; Won Koo Lee (Jurnal Pendidikan Sains Indonesia, 2026)
Assessment plays an important role in measuring the achievement of 21st-century skills, particularly reading literacy, numeracy, and critical thinking. However, assessment practices that remain focused on rote memorization have not fully captured these skills in an integrated manner. In addition, the integration of local cultural contexts into science assessments is still limited. Therefore, this study aims to develop a reading literacy and numeracy assessment instrument incorporating West Java ethnoscience contexts on the topic of thermochemistry that is appropriate for assessing students’ critical thinking skills in terms of content validity. This study employed a test design and development method involving five chemistry education experts as validators. The resulting product consists of 50 reading literacy and numeracy items that incorporate nine ethnoscience contexts in West Java: torch parade tradition, bandrek preparation, Kampung Kuta palm sugar, adu kuluwung tradition, peuyeum Bandung, biogas in Cibodas village, Kampung Naga traditional house, maranggi satay, and bathing around kawah rengganis.  The results of the content validity indicate that all texts and test items were considered highly valid (CVR = 1; I-CVI = 1; S-CVI/ave = 1). These findings suggest that the alignment among chemistry concepts, reading texts, and test items has been adequately achieved. The validated instrument was then designed within a learning management system, namely moodle, as a digital-based trial medium and to support further improvement of the instrument quality during subsequent testing stages